ENETS standardized (synoptic) reporting for molecular imaging studies in neuroendocrine tumours. (20th October 2021) - Hicks, Rodney J.; Dromain, Clarisse; de Herder, Wouter W.; Costa, Frederico P.; Deroose, Christophe M.; Frilling, Andrea; Koumarianou, Anna; Krenning, Eric P.; Raymond, Eric; Bodei, Lisa; Sorbye, Halfdan; Welin, Staffan; et al.
Abstract: The European Neuroendocrine Tumor Society (ENETS) promotes practices and procedures that aim to improve the standard of care delivered to patients diagnosed with or suspected of having neuroendocrine neoplasia (NEN). At its annual Scientific Advisory Board Meeting in 2018, experts in imaging, pathology and clinical care of patients with NEN drafted guidance for the standardised reporting of diagnostic studies critical to the diagnosis, grading, staging and treatment of NEN. These included pathology, radiology, endoscopy and molecular imaging procedures. In an iterative process, a synoptic reporting template for molecular imaging procedures was developed to guide personalised therapies. Following pilot implementation and refinement within the ENETS Center of Excellence network, harmonisation with specialist imaging societies including the Society of Nuclear Medicine, European Association of Nuclear Medicine and the International Cancer Imaging Society will be pursued. Abstract : In an iterative process, a synoptic reporting template for molecular imaging procedures was developed by the European Neuroendocrine Tumor Society (ENETS) to guide personalised therapies. Following pilot implementation and refinement within the ENETS Center of Excellence network, harmonisation with specialist imaging societies including the Society of Nuclear Medicine, European Association of Nuclear Medicine and the International Cancer Imaging Society will be pursued.